GEOGRAFIYA PÁNIN OQÍTÍWDA DIDAKTIKALÍQ OYÍNLAR TEXNOLOGIYASÍNAN PAYDALANÍW - Gaypova, R.T.; Tolepov, E.T. (ILIM hám JÁMIYET, 2021)
This article focuses on improving the level of thinking and effectiveness of the lesson, as well as on improving the ways of forming students ’ knowledge, skills and abilities at geography lessons using didactic game technologies.